Economics of grids, clouds, systems, and services : 10th International Conference, GECON 2013, Zaragoza, Spain, September 18-20, 2013. Proceedings - Vanmechelen, Kurt; Rana, Omer F.; Altmann, Jorn (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 10th International Conference on Economics of Grids, Clouds, Systems, and Services, GECON 2013, held in Zaragoza, Spain, in September 2013. The 20 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in the following topical sections: business models, energy consumption, resource allocation, work in progress on resource allocation, work in progress on pricing, quality of service, work in progress on utility and ROI modeling.